An assessment of the coordination and coordination variability between the thorax and pelvis during a maximal instep kick - Gosling, J. A.; Needham, R. A.; Chockalingam, N. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of study was to assess coordination and coordination variability between the pelvis and thorax during a maximal instep kick (MIK) with the use of a modified vector coding technique. Nine university football players participated in this study. An optoelectronic motion capture system collected kinematic data on the dominant (DOM) and non-dominant (ND) side. The output from the vector coding technique was assigned to a coordination pattern classification that details the phase relationship between two segments, quantifies segmental dominancy, and provides information on segmental angle rotations. The results of this study and the reported coordination patterns of a MIK expands on current understanding of the tension arc (TA). Coordination variability was greater for the ND trials compared to the DOM trials. Overall, pelvis-thorax coordination and trunk angle kinematics are extremely influential when producing a high quality MIK.